Analysis of Quantity Take Off Deviation Using BIM Method (Case Study of Construction of a Satpol PP Building) - Fadlilah, Muhammad Reza Nur; Handayani, Fajar Sri; Rifai, Muji (Indonesian Journal Publisher, 2024)
Quantity Take Off (QTO) is in important process in the construction industry that calculates and estimates the amount of material needed to complete a construction project. This process includes detail analysis of design plans and technical specification to identify and calculate quantities. QTO results are used to create cost budgets, create project plans, and plan material procurement. This research explains the Building Information Modeling (BIM) application which uses Autodesk Revit software to calculate Quantity Take Off volume. The aim is to find out the difference between volume calculations using conventional methods and volume calculations using the BIM method and Quantity Take Off volumes in architectural work and structural work. A comparative analysis of conventional methods and the use of Autodesk Revit provide an overview of the efficiency and effectiveness of implementing BIM software in the Bantul Satpol PP Building Construction Project with a focus on structural an architectural work investigation studies. This research uses a case study methodology which includes a quantity survey using Building Information Modeling (BIM) techniques using Autodesk Revit and Microsoft Excel software. This research method includes preparatory steps, data collection techniques, 3D modeling, and data analysis based on volume the use of BIM software and conventional methods. Based on the survey results, the difference in volume calculations for architectural work is 9,68% and for structural work is 9,00%, this shows that volume calculations using the BIM method are smaller than using conventional methods.